2018
DOI: 10.17586/2220-8054-2018-9-3-401-409
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties and photocatalytic activity of nanocrystalline TiO2 doped by 3d-metal ions

Abstract: The influence of impurities on optical and photocatalytic properties was studied in a series of nanocrystalline TiO 2 with similar coherent scattering region sizes, phase compositions, surface areas and lattice parameters doped by Fe, Cr, Mn and V ions. Doping leads to an increase of absorption in the visible part of the spectrum due to the formation of additional levels in the band gap. In the case of Fe and Cr ions, d-d transitions are observed, whereas in the case of Mn and V ions, an additional band is ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…There are several approaches to suppressing the photocatalytic reactions on the surface of titania, including using amorphous titanium oxide, which has less photocatalytic activity than the crystalline phases [8]. Additionally, photocatalytic activity may be suppressed by doping the titanium oxide with metal ions [9][10][11] or modifying its surface composition [12][13][14]. Matsukura and Onoda showed that phosphate modification leads to photocatalytic activity suppression in TiO 2 -containing pigments [12].…”
Section: Introductionmentioning
confidence: 99%
“…There are several approaches to suppressing the photocatalytic reactions on the surface of titania, including using amorphous titanium oxide, which has less photocatalytic activity than the crystalline phases [8]. Additionally, photocatalytic activity may be suppressed by doping the titanium oxide with metal ions [9][10][11] or modifying its surface composition [12][13][14]. Matsukura and Onoda showed that phosphate modification leads to photocatalytic activity suppression in TiO 2 -containing pigments [12].…”
Section: Introductionmentioning
confidence: 99%
“…Dopants may create energy levels inside the bandgap, which helps to separate electron-hole pairs created by light and increases the e ciency of redox processes. Therefore, the lack of these dopants in undoped ZnO results in a lower photocatalytic effectiveness compared to doped versions, as shown in several studies [35,36]. Finally, the creation of surface imperfections or areas that might trap charge carriers, although important for affecting the behaviour of charge carriers, may not be strong enough at lower levels of doping to have a major effect on catalytic activity.…”
Section: Charge Transport and Optical Propertiesmentioning
confidence: 99%
“…9. In addition to particle size, phase composition, and optical characteristics, there may be other parameters that influence photocatalytic activity [32].…”
Section: Photocatalytic Performancementioning
confidence: 99%